2018
DOI: 10.1111/jth.14203
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies show synergistic effects of a procoagulant bispecific antibody and bypassing agents

Abstract: Background Investigational non-factor products such as emicizumab offer a treatment option for patients with hemophilia and inhibitors. However, their mechanism of action raises questions regarding safety when they are combined with treatments for breakthrough bleeding. Objectives To evaluate in vitro thrombin generation (TG) and clot formation for combinations of activated prothrombin complex concentrate (aPCC), recombinant activated factor VII (rFVIIa), and a sequence-identical analog of emicizumab (SIA). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 32 publications
4
92
2
2
Order By: Relevance
“…Endogenous fVIIIa has high affinity and specificity for factors IXa and X in the presence of a phospholipid surface in addition to a short half‐life and feedback regulatory mechanisms. Excess thrombin generation with fVIII in combination with emicizumab was not observed . Moreover, addition of VWF‐containing pdfVIII to haemophilia A plasma with emicizumab did not show an additive effect in thrombin generation studies .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Endogenous fVIIIa has high affinity and specificity for factors IXa and X in the presence of a phospholipid surface in addition to a short half‐life and feedback regulatory mechanisms. Excess thrombin generation with fVIII in combination with emicizumab was not observed . Moreover, addition of VWF‐containing pdfVIII to haemophilia A plasma with emicizumab did not show an additive effect in thrombin generation studies .…”
Section: Discussionmentioning
confidence: 87%
“…Emicizumab, which has the ability to bind factors IXa, IX, Xa and X, is constitutively active in plasma and does not have a regulatory system that inhibits its mechanism of action . In vitro studies using a sequence‐identical analog of emicizumab demonstrated excess thrombin generation in combination with aPCC . The authors postulated that the combination of these two drugs induces a hypercoagulable state that may contribute to thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant use of activated prothrombin complex concentrates (aPCC) such as FEIBA ® (FEIBA NF, Baxalta US Inc, a Takeda company) for controlling breakthrough bleedings in doses exceeding 100 U/kg/24 h with a duration of treatment longer than 24 hours in patients treated with emicizumab has been associated with the development of thrombotic microangiopathies (TMA) and venous thrombotic events . In vitro studies have confirmed a synergistic effect between emicizumab and aPCC . No cases of thrombosis or TMA have been reported in the literature so far following administration of recombinant FVIIa (rFVIIa, eptacog alpha, NovoSeven ® ; Novo Nordisk) in patients receiving emicizumab .…”
Section: Introductionmentioning
confidence: 99%
“…5 To our knowledge, there is one published case report and one in vitro study that have proposed using TGA to monitor emicizumab therapy during concomitant FVIII BPA therapy. 8,9 Therefore, to better understand the effects of emicizumab on routine and global coagulation assays, we report herein the results from two patients that received emicizumab prophylaxis. Notable laboratory findings following emicizumab dosing include the spurious "normal" aPTTs in the 20-25 second range, respectively, and the undetermined FVIII levels at both 1 and 2 months following therapy.…”
mentioning
confidence: 99%